wilayah jelajah dan jenis pohon yang sering dimanfaatkan oleh joja (presbytis potenziani) di siberut utara - , DIDIK SYAIFUDIN, drh. Subeno, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Joja is one of four endangered primates in Siberut Island. Hunting and habitat loss are two things which the most threatening of Jojaâs sustainability. Habitat loss affect to home rangeâs Joja, so that sometime Joja can found in agricultural field. This condition caused Joja more easily to hunt and used for consumption by people. The aim of research are to find out the home range of Joja and knowing the tree species which most frequently used in that home range. This is as one of the types of conservation efforts to Joja. The method of research were by following the movement from morning till evening, at 06.00 until 18.00. GPS used to collected the home range data. Tree species data taken simultaneously while collecting home rangeâs data. Then, home rangeâs data analyzed with Minimum Convex Polygon by used Home Range Tools in ArcGIS 9.3.Tree species data processed with Microsoft office Excel 2010 software. Data were displayed in a table and pie chart, and the analyzed descriptive. The result of this research showed the home range of two group Joja researched is about 14,428 to 22,754 ha. The utilization of tree species based activity categories. The result was Sibuluk tolobo (Joni) and Langgurek (Junaedi) are the most dominant tree species for feeding activity. Sibeumunte (Joni) and Gutgut (Junaedi) become the most dominant for in active. Travelling activity most commonly used in Sibeumunte (Joni) and Logauna (Junaedi). Social activity of Joja done in Posa (Joni) and Kalibangbak (Junaedi).